Enhanced Liberation of Soluble Sugar, Protein, and R-Phycoerythrin Under Enzyme-Assisted Extraction on Dried and Fresh Gracilaria gracilis Biomass - Phuong, Hengsim; Massé, Anthony; Dumay, Justine; Vandanjon, Laurent; Mith, Hasika; Legrand, Jack; Arhaliass, Abdellah (Frontiers in Chemical Engineering, 2022)
This study aims to investigate the bio-refinery process through an enzyme-assisted extraction (EAE) on freeze-dried and fresh macroalgae Gracilaria gracilis, for the release of water-soluble components (R-Phycoerythrin, proteins, and sugar). Three enzymes: cellulase, protease, and enzyme cocktail (mixture of cellulase and protease) were applied in the study. Results showed that freeze-dried biomass yielded the highest target components in the presence of enzyme cocktail while fresh biomass was more compatible with a single enzyme, either protease for the release of R-PE and protein, or cellulase for sugar. The extraction of protein and sugar was improved by 43 % and 57 % from fresh biomass compared to dried biomass. The difference of biomass status was shown to affect the required enzyme and recovery yield during the extraction process. Employing an enzyme cocktail on freeze-dried biomass boosted the extraction yield which was probably from the complementary effect between enzymes. On the other hand, single enzyme handled better on fresh biomass, giving economic benefits (enzyme limitation, drying stage) for further implementation of the bio-refinery process. Thus, biomass treatment (fresh or freeze-dried) and enzyme type determined the efficiency of enzyme-assisted extraction according to the target components.